UNDERSTANDING THE FORMATION OF BOARDING HOUSE RENT PRICES: RESEARCHING THE PERSPECTIVES OF OWNERS AND TENANTS AROUND THE CAMPUS OF UNIVERSITAS KRISTEN INDONESIA PAULUS - Arliana Lenong; Oktaviara Bunga; Eva Ulandari; Natalia Paranoan; Maiercherinra Daud (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to thoroughly analyze the factors considered, tenants' perceptions, and strategies used by boarding house owners in setting rental prices. It employs a qualitative approach with a case study method. Data were collected through in-depth interviews with two boarding house owners and six tenants, as well as through direct observation of the boarding houses' facilities, services, and environments. The findings indicate that the main factors influencing rental prices are tenant comfort, facility completeness, cleaning services, security, parking availability, and strategic location. There are differences in the emphasis on price-determining factors between the two owners: Kinawa focuses more on comfort and location, while Otomona emphasizes complete facilities, cleaning services, and parking. Tenants generally perceive rental prices positively, considering them aligned with the facilities and services received. The owners’ strategies for setting prices include conducting market surveys, implementing an “open-close boarding house” system, and utilizing social media for promotion. This study also reveals that boarding house rental prices are determined by a combination of economic factors, varying managerial strategies among owners, and tenants’ perceived value.